Teleoperated tractor : development of a graphical user interface - Danielsson, Peter (2008)
This thesis is about the development of a graphical user interface for the teleoperated tractor IceMaker I. There are companies in Arjeplog, Sweden that provide winter test services for vehicle and component manufacturers from all over the world. One of the leading service providers in Arjeplog is IceMakers. They have during 30 years developed into a full service supplier to their clients. The services include arranging accommodation for the company personnel, providing components and equipment desired by the customer, and the most important task of all: making the ice tracks (often on the lakes), varying in shapes and sizes depending upon the type of testing being conducted. There is a major risk factor involved in the maintenance of the tracks. Running a tractor on the lake ice is not safe since the ice might break. The tractor could end up at the bottom of the lake with the driver trapped inside. IceMakers want a teleoperated tractor in order to decrease the risks for the personnel maintaining the tracks. Another benefit with a teleoperated tractor is that it provides the possibility to extend the winter test season. IceMakers have submitted the development of the control system to a project group at Luleå University of Technology. To enable teleoperation, the tractor has been equipped with a computer, some sensors and other necessary equipment. The user controls the tractor with a joystick, and gets video and data feedback from the tractor. The purpose of this thesis was to develop a user friendly graphical user interface (GUI) for the teleoperated tractor, and also to add support for two new units to the system: a DSP3000 gyro and a GPS receiver. Modifications of the old controller program have been performed in order to make it compatible with the new devices and the GUI. The program has also been restructured in order to make it easier to expand it in the future. Another improvement of the software is increased safety with the addendum of a watchdog. The GUI is written in Java. It can show video from two ...